Developing a framework for assessing equity in contributions to the global goal on adaptation as part of the global stocktake - Barkai, Kalia (Department of Environmental and Geographical Science, 2024)
The global stocktake (GST) aims to assess collective progress in mitigation, adaptation, and the means of implementation and support as outlined in Article 14 of the Paris Agreement. The stocktake will be undertaken considering equity and the best available science. As a result, the GST requires a framework for assessing equity in mitigation, adaptation, and support. While mitigation has been more frequently defined based on allocations of “fair shares” in terms of emissions responsibility and targets, it is less clear how equity can be assessed in contributions to the global goal on adaptation (GGA). This is due to the diversity of pathways for enhancing adaptive capacity, strengthening resilience, and reducing vulnerability to climate change. Equity in the GGA is highly intertwined with issues of justice as those least responsible for climate change are most vulnerable to its impacts and have little to no resources for adaptation. Moreover, although adaptation actions are taken on the local level, the GGA is a collective goal. An effective framework for an equity assessment in the GST would have further benefits, including: guiding equity-driven approaches to National Adaptation Plans (NAPs), acting as an ambition enabler for the Parties who believe that climate change efforts are fairly shared, and highlighting how equity considerations can be improved between the GSTs. This thesis raises and investigates the following questions: what metrics exist for assessing equity in national contributions to the GGA? how appropriate are existing indicators for assessing equity in national contributions to the GGA? and what could an effective framework for assessing equity in national contributions to the GGA look like? This research aims to answer these questions through a systematic review of literature on equity metrics in adaptation programmes on the national and international scale. Building from a narrative synthesis and keyword analysis of the references collected, this research develops a rubrics-based framework for assessing equity in the GGA as part of the GST. The framework is founded on four dimensions of equity: distributive, procedural, recognitional, and intergenerational justice. To test the framework's applicability to a specific contribution to the GGA, and to inform the framework's effectiveness for collective assessment in the GST, it is applied to the South African National Climate Change Adaptation Strategy (NCCAS). A summary diagram is developed which demonstrates that whilst South Africa's NCCAS shows some promise to mainstreaming equity in the distributive justice dimension, it could still be more comprehensive about the plans relating to procedural and recognitional justice, and fails to achieve equity in intergenerational justice